Respostas das emissões otoacústicas por produto de distorção em presença de perda auditiva neurossensorial - Renata Prazeres Moura (2016)
Introduction: Besides evaluating the functional integrity of the other hair cells, the responses of the otoacoustic emissions test is a tool to estimate hearing thresholds of people with cochlear disfunctionand the types actually used in the clinic routine are the transient evoked otoacoustic emissions and distortion products. Certain conditions cause destruction in parts of the outher hair cells, but preserving a percentage, the so-called residual outher hair cells. However the current protocols still fail to investigate the behavior of residual outher hair cells, after all the usual stimulation levels are considered insufficient and, therefore, necessary to raise the intensity of stimulation. Objective: To study the effect of stimulation intensity variation on the responses of distortion products in subjects with mild, moderate or severe sensorineural hearing loss using a new protocol to register the otoacoustic emissions. Methods: This is a cross-sectional observational study, composed of 38 participants, of both sexes, aged between 8 and 90 years, with diagnosis of mild, moderate or severe hearing loss, from the Hearing Health Service of the Hospital of the Federal University of Minas Gerais. The following procedures were performed: anamnesis, otoscopy, pure tone audiometry, speech audiometry, tympanometry, distortion product and residual otoacoustic emissions using a protocol develop for verification of the phases of responses, to identify the physiological responses. Responses recorded in residual otoacoustic emissions were considered "present" when it came to physiological responses, "absent" or "artifact" when it was instrumental responses. Descriptive analysis of the categorical and continuous variables was performed. The results of the residual otoacoustic emissions were correlated with pure tone thresholds. Statistical analysis was performed using the Mann-Whitney test and ANOVA with Bonferroni correction. Results: The study included 38 participants with an average age of 54.63 years. The total included ears was 72. On residual otoacoustic emissions test, at a frequency of 1300Hz, there was statistically significant difference between the groups with the result "absent" and "present" and between the groups with "artifact" and "present"; and in the frequency of 9 2000Hz between the groups with the result of "absent" and "present." By analyzing the average found in the audiometry and the results of residual emissions, only the frequency of 1300Hz showed a statistically significant association in all groups. However, the frequency of 2000Hz showed a statistically significant relationship between the "absent" and "present" result and "artifact" and "present." By correlating the results of the audiometry and the amount of residual emissions, there was positive correlation for the frequencies of 1000 Hz and 4000 Hz. The "artifact" was mostly recorded in the higher frequencies: 56.2% in 3000 Hz and 58.2% in 4000 Hz. Conclusion: The increased stimulation intensity in the otoacoustic emissions test can aid in the study of residual outher hair cells, as long as a protocol is used to check the correctness of the responses. The proposed protocol was useful, since it differentiates a physiological response of an artifact, thus avoiding misdiagnosis. However, further studies are needed with different populations, ages and different etiologies, for further deepening about cochlear function in the presence of hearing loss.